Fabrication of Solvent-Free Electrodes

By blending the aqueous adhesive dispersion with the dry active powder electrode material and applying it to the conductive substrate, the environmental and energy consumption problems of wet and dry methods in electrode manufacturing are solved, and the high performance of the electrode is achieved and Low cost preparation, providing the advantages of uniform distribution and low energy consumption.

CN113889658BActive Publication Date: 2025-01-07阿科玛股份有限公司
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202111172267.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2014-06-03
Filing Date
2015-06-03
Publication Date
2025-01-07
Estimated Expiration
2035-06-03

AI Technical Summary

Technical Problem

In the existing electrode manufacturing methods, the wet method requires a large amount of solvent evaporation, resulting in a large environmental impact and high energy consumption. The dry method has the problems of adhesive particles agglomeration and non-uniform distribution, making it difficult to achieve low-cost and high-performance electrode preparation.

Method used

The aqueous adhesive dispersion is blended with the material for forming electrodes in a dry active powder form, and applied to the conductive substrate, and the electrode is formed by a uniform blend, and a fluoropolymer is used as a preferred adhesive to provide a small particle size. and good particle distribution, reducing adhesive use and energy consumption.

Benefits of technology

The uniform adhesive particle distribution of the electrode and the interconnection of the active materials are achieved, manufacturing costs and energy consumption are reduced, environmental pollution is reduced, and the performance and use efficiency of the electrode are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113889658B_ABST
    Figure CN113889658B_ABST
Patent Text Reader

Abstract

The present invention relates to an electrode formed by blending a dry active powdered electrode-forming material with an aqueous binder dispersion, and subsequently adhering the wet binder / dry active powdered electrode-forming material blend to a conductive substrate to produce an electrode. The aqueous binder is preferably a fluoropolymer, and more preferably polyvinylidene fluoride (PVDF). The hybrid method provides good dispersion and small particle size of a wet method, as well as energy savings and reduced environmental impact of a dry method. The resulting electrode is useful in an energy storage device.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Divisional Application Instructions

[0002] This application is a divisional application of an invention patent application with an application date of June 3, 2015, an international application number of PCT / US2015 / 033881, a national application number of 201580029238.X after entering the Chinese national phase, and titled "Manufacturing of Solvent-Free Electrodes". Field of the Invention

[0003] The present invention relates to an electrode formed by blending a dry active powdered electrode-forming material with an aqueous binder dispersion, and subsequently adhering the wet binder / dry active powdered electrode-forming material blend to a conductive substrate to produce an electrode. The aqueous binder is preferably a fluoropolymer, and more preferably polyvinylidene fluoride (PVDF). The hybrid method provides good dispersion and small particle size of a wet method, as well as energy savings and reduced environmental impact of a dry method. The resulting electrode is useful in an energy storage device. Background of the Invention

[0004] The electrodes are used in energy storage devices including, but not limited to, batteries, capacitors, supercapacitors, secondary batteries of non-aqueous type, and the like.

[0005] Currently, there are two main means for producing electrodes: a "wet" method and a "dry" method. In the wet method, a polymer binder in the form of a solvent solution or dispersion is blended with one or more active powdered electrode-forming materials to form a slurry dispersion or paste. The dispersion or paste is then applied to one or both surfaces of a conductive substrate and dried to form a viscous composite electrode layer. The electrode layer can then be calendered. This method is shown in US 5,776,637 and US6,200,703, where a fluoropolymer binder is dissolved in NMP. An improvement in solvent solutions is the use of aqueous fluoropolymer dispersions as binders as described in US 2010 / 0304270 and US 2012 / 0015246. Advantageously, in the aqueous dispersion method, the polymer binder remains as small discrete particles - and those particles only bind the active electrode material at discrete points - resulting in the interconnectivity of the active electrode particles, rather than as a coating formed on the active particles by a polymer solution. Because most of the active electrode material is not covered by the binder, there is less insulation, less heat buildup, and better conductivity. In addition, aqueous binders offer environmental benefits over organic solvents, and less binder can be used because the dry active powdered electrode-forming material is essentially spot welded rather than fully coated.

[0006] The second method for forming an electrode is by a dry process. In a dry process, a dry polymer powder is dry blended with a dry active powdered electrode-forming material - often under high shear in which the mixture is fibrillated - and the dry blend is formed into a film adhered to a conductive substrate, or the dry blend is directly applied to and pressed onto the conductive substrate by means such as calendering. Dry electrode methods are described in US 7.791,860, US 7,791,861, US 8,072,734, US 8,591,601, and US2011 / 0165318.

[0007] The problem with wet processes is that large amounts of solvent have to be evaporated - this has negative environmental impacts and also requires a lot of energy to remove.

[0008] The problem of dry process is that the dry particles of adhesive polymer tend to agglomerate during the drying process or during storage, especially if these adhesive particles are soft. Agglomerated polymer adhesive particles are difficult to be evenly distributed throughout the blend. When it is desired that a low amount of adhesive is used to maximize performance and also minimize cost, this is especially a problem.

[0009] There is a desire to obtain the small particle size and good distribution of polymeric binders as found in aqueous dispersion coating processes, but with the advantages of reduced energy consumption of drying as found in dry processes and little or no environmentally undesirable solvent waste.

[0010] Surprisingly, it has now been discovered that a hybrid process can provide advantages over both wet and dry processes, resulting in synergistic positive properties of the formed electrode. In the hybrid process, an aqueous dispersion of binder is added to the dry active electrode-forming material, good distribution of small, discrete fluoropolymer binder particles occurs, and the water added with the dispersion is easily removed with heat applied during the electrode forming process. Advantageously, the dispersion is more uniform and the dispersed polymer particles do not agglomerate, providing the best of both processes.

[0011] Other advantages include lower manufacturing costs, energy savings, and better dispersion of the binder, which in turn can reduce binder usage. SUMMARY OF THE INVENTION

[0012] The invention relates to a method for forming an energy storage device, the method comprising the following steps

[0013] a) forming an aqueous binder dispersion;

[0014] b) adding the binder dispersion to the dry active powdered electrode-forming material so as to form a homogeneous blend, and

[0015] c) applying the homogeneous blend to at least one surface of a conductive substrate to form an electrode.

[0016] The invention further relates to an electrode formed by the method having a uniform distribution of binder particles and interconnectivity of the dry active powdered electrode-forming material. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 is the SEM of Example 1.

[0018] Figure 2 is the SEM of Example 2.

[0019] Figure 3a and 3b is the SEM of comparative example 1

[0020] Figure 4 is the SEM of Example 6.

[0021] Figure 5 is the SEM of Comparative Example 2.

[0022] Figure 6 is the SEM of Comparative Example 3.

[0023] Detailed description of the invention

[0024] All references cited in this application are hereby incorporated by reference. Unless otherwise indicated, all percentages in a composition are by weight; and unless otherwise indicated, all molecular weights are given as weight average molecular weight.

[0025] Polymer dispersion adhesives

[0026] The polymer dispersion useful as a binder in the present invention can be an aqueous dispersion of discrete particles of one or more polymers, preferably thermoplastic polymer particles. Useful polymers include, but are not limited to, fluoropolymers, SBR, ethylene vinyl acetate (EVA), acrylic polymers, polyurethanes, styrene polymers, polyamides, polyesters, polycarbonates, and thermoplastic polyurethanes (TPU).

[0027] Preferably, the binder is a fluoropolymer. Useful fluoropolymers are thermoplastic homopolymers and copolymers having greater than 50 weight percent fluorine-containing monomer units, preferably more than 65 weight percent, more preferably greater than 75 weight percent and most preferably greater than 90 weight percent of one or more fluorine-containing monomers. Useful fluorinated monomers for forming fluoropolymers include, but are not limited to, vinylidene fluoride (VDF or VF2), tetrafluoroethylene (TFE), trifluoroethylene (TrFE), chlorotrifluoroethylene (CTFE), hexafluoropropylene (HEP), vinyl fluoride (VF), hexafluoroisobutylene (HFIB), perfluorobutylethylene (PFBE), pentafluoropropylene, 3,3,3-trifluoro-1-propene, 2-trifluoromethyl-3,3,3-trifluoropropene, fluorinated vinyl ethers including perfluoromethyl ether (PMVE), perfluoroethyl vinyl ether (PEVE), perfluoropropyl vinyl ether (PPVE), perfluorobutyl vinyl ether (PBVE), longer chain perfluorinated vinyl ethers, fluorinated dioxoles, C4 and higher partially or fully fluorinated α-olefins, C3 and higher partially or fully fluorinated cycloolefins, and combinations thereof.

[0028] Particularly preferred fluoropolymers are polyvinylidene fluoride (PVDF) homopolymers and copolymers, and polytetrafluoroethylene (PTFE) homopolymers and copolymers. Although the present invention is applicable to all thermoplastic polymers, but in particular all fluoropolymers and copolymers, vinylidene fluoride polymers will be used to illustrate the present invention and are the preferred polymers.

[0029] In one embodiment, due to the lower crystallinity (or no crystallinity) of vinylidene fluoride copolymer, it is preferred, making it more flexible than semicrystalline PVDF homopolymer. The flexibility of adhesive provides the advantage of more flexible electrode and increased tensile strength and better adhesion characteristics that can better withstand manufacturing method. Such copolymers include those of vinylidene fluoride copolymerized with one or more comonomers selected from the group of at least 50 mole percent, preferably at least 75 mole %, more preferably at least 80 mole % and even more preferably at least 85 mole % and one or more selected from the group, the group is made up of the following: tetrafluoroethylene, trifluoroethylene, chlorotrifluoroethylene, hexafluoropropylene, vinyl fluoride, pentafluoropropylene, tetrafluoropropylene, trifluoropropylene, perfluoromethyl vinyl ether, perfluoropropyl vinyl ether and any other monomer easily copolymerized with vinylidene fluoride.

[0030] In one embodiment, there are up to 30%, preferably up to 25%, and more preferably up to 15% by weight of hexafluoropropylene (HFP) units and 70% or more, preferably 75% or more, more preferably 85% or more or more VDF units by weight in the vinylidene fluoride polymer. It is desirable that the HFP units are distributed as evenly as possible to provide a PVDF-HFP copolymer with excellent dimensional stability in the final use environment.

[0031] PVDF for use in the electrode composition preferably has a high molecular weight. By high molecular weight, as used herein, it is meant that the PVDF has a molecular weight of 100 s at 450°F according to ASTM method D-3835. -1 The melt viscosity is greater than 1.0 kpoise, preferably greater than 5 kpoise, more preferably greater than 10 kpoise, and most preferably greater than 15 kpoise, as measured at 370°C.

[0032] The PVDF used in the present invention is generally prepared by means known in the art, using aqueous free radical emulsion polymerization - although suspension polymerization, solution polymerization and supercritical CO2 polymerization methods can also be used. In the usual emulsion polymerization method, deionized water, a water-soluble surfactant capable of emulsifying the reactant mass during the polymerization process, and an optional paraffin antifouling agent are charged to the reactor. The mixture is stirred and deoxygenated. A predetermined amount of chain transfer agent, CTA, is then introduced into the reactor, the temperature of the reactor is raised to the desired level and vinylidene fluoride (and possibly one or more comonomers) is fed into the reactor. Once the first charge of vinylidene fluoride is introduced and the pressure in the reactor has reached the desired level, an initiator emulsion or solution is introduced to start the polymerization reaction. The temperature of the reaction can be changed according to the characteristics of the initiator used and a person of ordinary skill in the art will know how to do this. Typically the temperature will be from about 30°C to 150°C, preferably from about 60°C to 120°C. Once the desired amount of polymer has been reached in the reactor, the monomer feed is stopped, but the initiator feed is optionally continued to consume residual monomer. The residual gas (containing unreacted monomer) is vented and the latex is recovered from the reactor.

[0033] The surfactant used in the polymerization reaction can be any surfactant known in the art to be useful in PVDF emulsion polymerization, including perfluorinated, partially fluorinated and non-fluorinated surfactants. Preferably, the PVDF emulsion of the present invention is free of fluorinated surfactants, wherein no fluorinated surfactants are used in any part of the polymerization reaction. The non-fluorinated surfactants useful in the PVDF polymerization reaction can be both ionic and non-ionic in nature, including but not limited to: 3-allyloxy-2-hydroxy-1-propane sulfonate, polyvinylphosphonic acid, polyacrylic acid, polyvinylsulfonic acid and its salts, polyethylene glycol and / or polypropylene glycol and its block copolymers, alkylphosphonates and siloxane-based surfactants.

[0034] PVDF polymerization produces a kind of latex, this latex generally has by weight 10 to 60 percent, preferably 10 to 50 percent solid level, and has less than 500nm, preferably less than 400nm and more preferably less than 300nm weight average particle size.This weight average particle size is generally at least 20nm and preferably at least 50nm.Extra adhesion promoter can also be added to improve bonding characteristics and provide irreversible connectivity.A small amount of one or more other water miscible solvents (such as ethylene glycol) can be mixed in this PVDF latex to improve freeze-thaw stability.

[0035] Dry active powder material for electrode formation

[0036] The aqueous binder dispersion is added as part of an aqueous binder dispersion composition to one or more types of dry active powdered electrode-forming materials. The properties of these dry active powdered electrode-forming materials depend on whether the composition will be used to form a positive electrode or a negative electrode. In the case of a positive electrode, the active electrode material can be an oxide, sulfide or hydroxide of lithium and a transition metal (including but not limited to cobalt, manganese, aluminum, titanium, or nickel, and iron phosphate, manganese phosphate). Complex salts of lithium and triple salts are also contemplated. Preferred positive electrode materials include, but are not limited to LiCoO2, LiNi x Co 1-x O2, LiMn2O2, LiNiO2, LiFePO4, LiNi x Co y Mn z O m 、LiNi x Mn y Al z O m, where x+y+z=1 and m is an integer representing the number of oxygen atoms in the oxide to provide an electron-balanced molecule; and lithium-metal oxides such as lithium cobalt oxide, lithium iron phosphate, lithium manganese phosphate, lithium-nickel oxide, and lithium-manganese oxide.

[0037] In the case of a negative electrode, the active material is generally a carbonaceous material, a nano titanate, or other matrix that can be doped with lithium ions. Useful carbonaceous materials include, but are not limited to, graphite, artificial graphite, carbon, carbon black, activated carbon, acetylene black, phenolic resin, asphalt, tar, etc. Carbon fiber can also be used in the present invention.

[0038] The ratio of PVDF solids to dry active powdered electrode-forming material is from 0.5-25 parts by weight of PVDF solids to 75 to 99.5 parts by weight of powdered electrode material, preferably from 0.5-15 parts by weight of PVDF solids to 85 to 99.5 parts by weight of powdered electrode material, more preferably from 1-10 parts by weight of PVDF solids to 90 to 99 parts by weight of powdered electrode material, and in one embodiment from 2-8 parts by weight of PVDF solids to 92 to 98 parts by weight of powdered electrode material. If less PVDF is used, full interconnectivity may not be achieved, and if more PVDF is used, there is a reduction in conductivity, and also the composition takes up volume and adds weight - and one use of the composition is for very small and light batteries.

[0039] Waterborne polymer adhesive composition

[0040] The aqueous fluoropolymer binder dispersion of the present invention may optionally be combined with one or more additives to form an aqueous fluoropolymer binder dispersion composition prior to addition to the dry active powdered electrode-forming material. These optional additives include, but are not limited to, surfactants, anti-settling agents, wetting agents, thickeners, rheology modifiers, fugitive adhesion promoters, fillers, defoamers, pH buffers, and other adjuvants typically used in water-based formulations while meeting the desired electrode requirements.

[0041] Surfactant / Anti-settling Agent

[0042] Fluoropolymer dispersion compositions of the present invention contain 0 to 10 parts, preferably from 0.1 to 10 parts, and more preferably 0.5 to 5 parts of one or more anti-settling agents and / or surfactants per 100 parts of water. In one embodiment, the level of anti-settling agents or surfactants is from 2.7 to 10 parts per 100 parts of water. These anti-settling agents or surfactants are added to the PVDF dispersion post-polymerization reaction to improve storage stability in general and provide additional stability during the slurry preparation process. Also during the polymerization process, the surfactant / anti-settling agent used in the present invention can be added in advance before polymerization, continuously fed during polymerization, partially fed before polymerization and then fed during polymerization, or fed after polymerization starts and for a period of time.

[0043] Useful anti-settling agents include, but are not limited to, ionic materials such as salts of alkyl sulfates, sulfonates, phosphates, phosphonates (e.g., sodium lauryl sulfate and ammonium lauryl sulfate) and partially fluorinated salts of alkyl sulfates, carboxylates, phosphates, phosphonates (e.g., those sold by DuPont under the CAPSTONE trademark), and nonionic surfactants such as the TRITON X series (from Dow) and the PLURONIC series (from BASF). In one embodiment, only anionic surfactants are used. It is preferred that no fluorinated surfactants are present in the composition, which are residual surfactants from the polymerization process, or additional post-polymerization reactions in forming or concentrating the aqueous dispersion.

[0044] Wetting agent

[0045] Fluoropolymer composition of the present invention optionally contains 0 to 5 parts of water per 100 parts, preferably one or more wetting agents from 0 to 3 parts. Surfactant can act as a wetting agent, but wetting agent can also include non-surfactant. In certain embodiments, the wetting agent can be an organic solvent. It has been found that the presence of optional wetting agent allows uniform dispersion of one or more powdered electrode materials to the aqueous dispersion of vinylidene fluoride polymer. Some electrode materials, such as carbonaceous materials, will not be dispersed in aqueous dispersions without the use of wetting agents. Useful wetting agents include but are not limited to ionic and nonionic surfactants, such as TRITON series (from Dow) and PLURONIC series (from BASF), and organic liquids compatible with aqueous dispersions, including but not limited to NMP, DMSO and acetone.

[0046] Thickeners / rheology modifiers

[0047] The fluoropolymer composition of the present invention may contain 0 to 10 parts, preferably from 0 to 5 parts, of one or more thickeners or rheology modifiers per 100 parts of water. A water-soluble thickener or rheology modifier is added to the above dispersion to prevent or slow down the settling of the powdered electrode material while providing an appropriate slurry viscosity for the casting process. Useful thickeners include, but are not limited to, the ACRYSOL series (from Dow Chemical); partially neutralized poly(acrylic acid) or poly(methacrylic acid), such as CARBOPOL from Lubrizol; and carboxylated alkyl celluloses, such as carboxylated methyl cellulose (CMC). Adjustment of the pH of the formulation can improve the effect of some thickeners. In addition to organic rheology modifiers, inorganic rheology modifiers may also be used alone or in combination. Useful inorganic rheology modifiers include, but are not limited to, inorganic rheology modifiers, including, but not limited to: natural clays such as montmorillonite and bentonite, artificial clays such as laponite, and others such as silica, and talc.

[0048] Short-acting adhesion promoter

[0049] A fugitive adhesion promoter is optionally added to aid in the interconnectivity of the active powdered electrode-forming material in the electrode formed by the method of the present invention. By "fugitive adhesion promoter" as used herein is meant an agent that increases the interconnectivity of the active particles after being applied to a conductive substrate. The fugitive adhesion promoter can then be removed from the formed electrode mass by evaporation (for chemicals) or by dissipation (for added energy).

[0050] The short-acting adhesion promoter can be a chemical material, an energy source combined with pressure, or a combination, used in an effective amount to cause the interconnectivity of the various components of the aqueous composition during the formation of the electrode. For chemical short-acting adhesion promoters, the composition contains 0 to 150 parts of water per 100 parts, preferably 1 to 100 parts, and more preferably one or more short-acting adhesion promoters from 2 to 30 parts. Preferably, this is an organic liquid, which is soluble or miscible in water. This organic liquid acts as a plasticizer for PVDF particles, making them sticky and able to act as discrete adhesion points during the drying step. PVDF polymer particles can soften, flow and adhere to powdered materials during the manufacturing process, thereby producing an electrode with high irreversible connectivity. In one embodiment, the organic liquid is a latent solvent, which is a solvent that does not dissolve or substantially expands PVDF resin at room temperature, but will solvate PVDF resin at elevated temperatures. In one embodiment, a useful organic solvent is N-methyl-2-pyrrolidone. Other useful short-acting adhesion promoter agents include, but are not limited to, dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide (DMSO), hexamethylphosphoramide, dioxane, tetrahydrofuran, tetramethylurea, triethyl phosphate, trimethyl phosphate, dimethyl succinate, diethyl succinate, and tetraethyl urea.

[0051] In the case where energy is used as a fugitive adhesion promoter, useful energy sources include, but are not limited to, heat, infrared radiation, and radio frequency (RF). For heating only, the temperature during treatment of the PVDF composition on the electrode should be about 20°C to 50°C above the melting point of the polymer. When energy only is used as a fugitive adhesion promoter, it is preferred to combine heat with pressure - such as a calendaring step, for good interconnectivity.

[0052] The aqueous fluoropolymer composition can be diluted as needed to optimize processing. Higher solid compositions are preferred because less water must be removed during the process, however a certain viscosity is required to optimize dispersion flow rate when added to the dry active powdered electrode-forming material.

[0053] Conductive substrate:

[0054] Once the binder / active electrode particle blend is formed, it is applied to a conductive substrate to form an electrode. The conductive substrate is generally thin and usually consists of a foil, grid or mesh of a metal such as aluminum, copper, lithium, iron, stainless steel, nickel, titanium, or silver.

[0055] method

[0056] Dry electrode processing is attractive because it eliminates solvents and associated equipment and processing costs, which can significantly reduce the total battery cost. One challenge in dry electrode processing is to achieve uniform dispersion of carbon and binder particles in a solid mixture. Prior art blends PVDF-based binder powders into carbon or carbon / active material mixtures. PVDF-based binder powders consist of agglomerates of primary particles. The agglomerate structure cannot be easily dispersed into separate primary particles using normal dry methods for powder mixing / dispersion. Agglomerates prevent close contact between primary binder particles and carbon / active materials and reduce the efficiency / utilization of the binder.

[0057] To achieve optimal dispersion of binder particles, the present invention includes spraying the binder latex into dry carbon and / or active material. Because the binder exists as separate primary particles in the latex, our method will cause intimate contact between the binder primary particles, carbon and / or active material.

[0058] One of ordinary skill in the art can envision several methods by which the aqueous binder dispersion can be combined with the dry active powdered electrode-forming material to form a homogenous blend based on the following non-limiting examples.

[0059] In one embodiment, the dry active powdered electrode-forming material is placed in a high shear mixer, such as a jet mill or a Henschel mixer, and mixing is initiated. The fluoropolymer dispersion can then be added to the dry powdered material at a slow rate over a period of several minutes to several hours, depending on the volume and speed of mixing in the container, to form a uniform, wet blend.

[0060] In another embodiment, the dry active electrode powder particles can be spread and the binder dispersion can be atomized or sprayed onto the powder. The uniform distribution of the dispersion can be aided by using a drum to stir the spray powder. Importantly, the polymer dispersion is shear-stable so as to maintain integrity during spray application. Shear stability can be obtained by different means as known in the art, including the use of additives described previously.

[0061] The binder / dry active powdered electrode-forming material blend of the present invention can be applied to one or both sides of a conductive substrate by means known in the art. In one embodiment, the blend is formed into a film by powder coating or casting, and the film is adhered to the conductive substrate using an adhesive as known in the art.

[0062] In another embodiment, the blend is deposited directly onto the conductive substrate and pressed onto the substrate by means such as calendering. The conductive substrate / blend composite may be heated to aid in the pressing process.

[0063] use

[0064] Electrodes formed by the methods of the present invention may be used to form electrochemical devices, including but not limited to batteries, capacitors, and other energy storage devices.

[0065] Examples

[0066] General:

[0067] The latex of the present invention is prepared by a typical method for preparing fluoropolymers using emulsifiers. These emulsifiers can be ionic or non-ionic, such as those containing blocks of polyethylene glycol, polypropylene glycol and / or polybutylene glycol. Preferably, the method and the fluoropolymer produced do not include fluorinated or partially fluorinated surfactants. The resulting fluoropolymer dispersions have good latex stability and shelf life and are free of coagulation. These preferred dispersions are completely free of fluorinated or partially fluorinated surfactants - wherein no fluorinated surfactants are used either in the synthesis or in post addition.

[0068] In the polymerization method, the emulsifier may be added in advance in its entirety before polymerization, continuously fed during polymerization, partially fed before polymerization and then fed during polymerization, or fed after polymerization is started and proceeds for a period of time.

[0069] Example 1

[0070] 345 pounds of deionized water, 250 grams of PLURONIC 31R1 (a non-fluorinated nonionic surfactant from BASF) and 0.3 pounds of propane were loaded into an 80-gallon stainless steel reactor. After evacuation, stirring was started at 23 rpm and the reactor was heated. After the reactor temperature reached the desired 100°C set point, VDF addition was started. The reactor pressure was then raised to 650 psi by loading about 35 pounds of VDF into the reactor. After the pressure of the reactor stabilized, 4.5 pounds of initiator solution were added to the reactor to initiate polymerization, the initiator solution being made of 1.0 wt% potassium persulfate and 1.0 wt% sodium acetate. The rate at which the initiator solution was further added was adjusted to obtain and maintain a final VDF polymerization rate of about 70 pounds / hour. The VDF homopolymerization was continued until about 150 pounds of VDF were introduced into the reaction mass. The VDF feed was stopped and the batch was allowed to react to completion at the reaction temperature to consume the residual monomers under reduced pressure. After 25 minutes, stirring was stopped and the reactor was cooled, emptied and the latex recovered. The solids in the recovered latex were determined by gravimetric techniques and were about 27% by weight and were 100% by weight according to ASTM method D-3835 at 450°F and 100 seconds. -1The melt viscosity of the resin was about 27 kp measured at 100° C. The melting temperature of the resin was measured according to ASTM method D-3418 and found to be about 162° C. The weight average particle size was measured by NICOMP laser light scattering instrument and found to be about 150 nm.

[0071] Example 2

[0072] 345 pounds of deionized water, 250 grams of PLURONIC 31R1 (non-fluorinated nonionic surfactant from BASF) and 0.6 pounds of ethyl acetate were loaded into an 80-gallon stainless steel reactor. After evacuation, stirring was started at 23 rpm and the reactor was heated. After the reactor temperature reached the desired 100°C set point, VDF and HFP monomers were introduced into the reactor, wherein the HFP ratio was 40 wt% of the total monomer. The reactor pressure was then raised to 650 psi by loading about 35 pounds of total monomer into the reactor. After the pressure of the reactor was stabilized, 5.0 pounds of initiator solution were added into the reactor to initiate polymerization, and the initiator solution was made of 1.0 wt% potassium persulfate and 1.0 wt% sodium acetate. Initially, the ratio of HFP to VDF was adjusted so as to reach 16.5% HFP in the feed relative to the total monomer. The rate at which the initiator solution is further added is also adjusted to obtain and maintain a final combined VDF and HFP polymerization rate of approximately 70 pounds per hour. The VDF and HPF copolymerization reaction is continued until approximately 160 pounds of monomer are introduced into the reaction mass. The HFP feed is stopped but the VDF feed is continued until approximately 180 pounds of total monomer is fed into the reactor. The VDF feed is stopped and the batch is allowed to react to completion at the reaction temperature to consume residual monomer under reduced pressure. After 40 minutes, the initiator feed and stirring are stopped and the reactor is cooled, emptied and the latex is reclaimed. The solids in the reclaimed latex are determined by gravimetric techniques and are approximately 32 weight % and are heated to 450°F and 100 seconds according to ASTM method D-3835. -1 The melt viscosity of the resin was about 28 kp measured at 100° C. The melting temperature of the resin was measured according to ASTM D3418 and found to be about 120° C. The weight average particle size was measured by a NICOMP laser light scattering instrument and found to be about 160 nm.

[0073] Example 3

[0074] 345 pounds of deionized water, 250 grams of PLURONIC 31R1 (non-fluorinated nonionic surfactant from BASF) and 0.35 pounds of ethyl acetate were loaded into an 80-gallon stainless steel reactor. After evacuation, stirring was started at 23 rpm and the reactor was heated. After the reactor temperature reached the desired 100°C set point, VDF and HFP monomers were introduced into the reactor, wherein the HFP ratio was 13.2 wt% of the total monomers. The reactor pressure was then raised to 650 psi by loading about 35 pounds of total monomers into the reactor. After the pressure of the reactor was stabilized, 3.5 pounds of initiator solution were added into the reactor to initiate polymerization, and the initiator solution was made of 1.0 wt% potassium persulfate and 1.0 wt% sodium acetate. Initially, the ratio of HFP to VDF was adjusted so as to reach 4.4% HFP relative to the total monomers in the feed. The rate at which the initiator solution is further added is also adjusted to obtain and maintain the final combined VDF and HFP polymerization rate of about 90 pounds per hour. The VDF and HPF copolymerization reaction is continued until about 160 pounds of monomer are introduced into the reaction mass. The HFP feed is stopped but the VDF feed is continued until about 180 pounds of total monomer are fed into the reactor. The VDF feed is stopped and the batch is allowed to react to consume residual monomers under reduced pressure at the reaction temperature. After 40 minutes, the initiator feed and stirring are stopped and the reactor is cooled, emptied and the latex is reclaimed. The solids in the recovered latex are determined by gravimetric techniques and are about 32 weight % and according to ASTM method D-3835 at 450 ° F and 100 seconds. -1 The melt viscosity of the resin was about 38 kp measured at 100° C. The melting temperature of the resin was measured according to ASTM method D-3418 and found to be about 152° C. The weight average particle size was measured by NICOMP laser light scattering instrument and found to be about 160 nm.

[0075] The above PVDF-based latexes of Examples 1-3 were then formulated into aqueous separator coating compositions and applied to the separators and dried.

[0076] Dry electrode processing

[0077] In order to illustrate the advantages of the present invention, the following tests / examples were conducted:

[0078] Examples 4 Dispersing the binder latex particles into the conductive carbon

[0079] 5.0 g of Arkema Inc. LBG latex (20% solids) was sprayed onto 1.0 g of conductive carbon (SuperP from Timcal). During spraying, the powder / latex mist was mixed by a magnetic stir bar at 180-240 rpm. The mist mixture was dried in a vacuum oven at 60°C for 2 hours. The dry mixture was then mixed in a centrifugal planetary mixer (Thinky) at 2000 rpm for 1 min using 5 mm zirconium oxide beads as grinding media to break up large crumbs. The dry powder mix morphology was observed by SEM. Typical SEM of Example 4 sample at Figure 1 . The spheres of about 130 nm are binder particles, while the particles of about 40 nm are carbon. Obviously, the binder is dispersed as primary particles and is uniformly and intimately mixed with the carbon particles.

[0080] Example 5: Dispersing binder latex particles into conductive carbon

[0081] 5.0 g of modified PVDF latex (20% solids) was sprayed onto 1.0 g of conductive carbon (SuperP from Temeco) by an ultrasonic atomizer (VC50 by Sonics). During spraying, the powder / latex mist was mixed at 180-240 rpm by a magnetic stirring bar. The mist mixture was dried in a vacuum oven at 60°C for 2 hours. The dry mixture was then mixed at 2000 rpm for 1 min in a centrifugal planetary mixer (Thinky) using 5 mm zirconium oxide beads as grinding media to break up large crumbs. Typical SEM images of the sample of Example 5 are shown in Figure 5. Figure 2 . The spheres of about 200 nm are binder particles, while the particles of about 40 nm are carbon. Obviously, the binder is dispersed as primary particles and is uniformly and intimately mixed with the carbon particles.

[0082] Comparative Example 1 .Dry blending of conductive carbon and binder powders

[0083] 0.3 g of conductive carbon (SuperP from Temeco) and 0.3 g of PVDF binder (KYNAR LBG) were mixed in a centrifugal planetary mixer (Thinky) at 2000 rpm for 2 min using 5 mm zirconia beads as grinding media. A 1:1 ratio of carbon to binder was chosen as this is typical in most cathode electrode compositions. The dry powder mix morphology was observed by SEM. Typical SEM images of the Comparative Example 1 sample are shown in Figure 2. Figure 3a and 3b Shown in. Figure 3a Shown is a binder powder (3-10 um size) coated with carbon particles (primary particles of approximately 40 nm). Figure 3bShown is a high magnification on the surface of a coated composite which is completely covered with carbon (structure with 40 nm primary particles), with almost no binder particles (approximately 130 nm) being visible.

[0084] Compare Figure 3b With Figure 1 and 2 In the examples of the present invention shown in FIG. 1 , one can see that the mixture produced by the latex dispersion method of the present invention shows uniform dispersion / mixing of carbon and binder primary particles, while dry powder blending only coats the surface of the binder agglomerates and does not break down the binder into primary particles.

[0085] Example 6 . Dry blended cathode mixture, latex spraying method of the present invention

[0086] LCO (Umicore D10), carbon (SuperP), and binder (Kynar LBG) were used in a ratio of 90:5:5. 0.6 g of the carbon / binder mixture from Example 4 (latex spray method) and 5.4 g of LCO were dry mixed by Thinky at 2000 rpm for 2 min. Typical SEM images of the Example 6 samples were obtained at Figure 4 The flat flake features are the binder (deformed due to shear / heating during mixing with the active material), while the ~40 nm particles are carbon. Using the latex spray method, the majority of the surface is the binder flakes as the carbon is evenly distributed in the carbon / binder composite structure.

[0087] Comparative Example 2 . Dry blended cathode mixture, method 1

[0088] LCO (Umicore D10), carbon (SuperP), and binder (Kynar LBG) were used in a ratio of 90:5:5. First, 0.3 g of carbon and 5.4 g of LCO were dry mixed by Thinky at 2000 rpm for 2 min, then 0.3 g of binder powder was added and mixed at 2000 rpm for 2 min. A typical SEM of Comparative Example 2 was Figure 5 The flat flake features are the binder, while the approximately 40 nm particles are the carbon. In this example, the majority of the surface in the carbon / binder composite is carbon.

[0089] Comparative Example 3 . Dry blended cathode mixture, method 2

[0090] LCO (Umicore D10), carbon (SuperP), and binder (Kynar LBG) were used in a ratio of 90:5:5. 0.6 g of the carbon / binder mixture from Example 4 (dry powder blending method) and 5.4 g of LCO were dry mixed by Thinky at 2000 rpm for 2 min. A typical SEM of Comparative Example 3 was Figure 6 The flat flakes are characteristic of the binder, while the particles of about 40 nm are carbon. The majority of the surface in this carbon / binder composite is carbon.

[0091] Example 6 and Comparative Examples 2 and 3 are compared by Figure 5 and 6 The dry powder blending atomization electrode shown in (comparison) is compared with the electrode obtained by Figure 4 Electrodes of the latex spraying method of the present invention in the present invention. Most of the exposed surface in Comparative Examples 2 and 3 is carbon particles, while in the case of the latex spraying method of the present invention, most of the surface is covered by the adhesive. This is due to the ability of the dispersed adhesive to form separate primary particles and evenly incorporate into the mixture. This increases the utilization of the adhesive and ensures a well-connected network of carbon, which will enhance battery electrode adhesion / binding and electrical performance.

[0092] Example 7 Electrode manufacturing using dry process

[0093] Using the dry blended electrode mixture in Example 6, electrode films can be made at room temperature or elevated temperature by established powder pressing techniques such as by a hydraulic tablet press, or a roller press. An example of producing electrodes for capacitor applications from dry powder blends using a roller press is disclosed in U.S. Pat. No. 7,295,423. The same method when applied to making battery electrodes from dry powder mixtures will be expected to form working battery electrodes.

Claims

1. A method for forming an energy storage device, the method comprising the steps of: a) forming an aqueous binder dispersion composition having discrete particles of one or more polymers, the composition having a solids level of 10 to 60 percent by weight, wherein the aqueous binder dispersion composition does not contain conductive carbon; b) adding the aqueous binder dispersion to one or more types of dry active powdered electrode-forming materials by spraying the aqueous binder dispersion into the dry active powdered electrode-forming materials to form a homogeneous wet blend, c) drying the homogeneous wet blend of the binder and dry active powdered electrode-forming material, and d) applying the homogenous blend to at least one surface of a conductive substrate to form an electrode.

2. The method of claim 1, wherein the adhesive is selected from the group consisting of: Fluoropolymers, SBR, ethylene vinyl acetate (EVA), acrylic polymers, polyurethanes, styrenic polymers, polyamides, polyesters, polycarbonates, and thermoplastic polyurethanes (TPU).

3. The method of claim 2, wherein the adhesive comprises a fluoropolymer.

4. The method of claim 3, wherein the fluoropolymer comprises at least 50 weight percent polyvinylidene fluoride homopolymer or copolymer.

5. The method of claim 3, wherein the fluoropolymer is a copolymer comprising from 5 to 30 weight percent of hexafluoropropylene and 70 to 95 weight percent of vinylidene fluoride monomer units.

6. The method of claim 3, wherein the fluoropolymer has a thermal conductivity according to ASTM method D-3835 at 450°F and 100 seconds. -1 A melt viscosity greater than 5 kpoise measured at 370°C.

7. The method of claim 3, wherein the fluoropolymer has a thermal conductivity according to ASTM method D-3835 at 450°F and 100 seconds. -1 A melt viscosity greater than 15 kpoise measured at 100 °C.

8. The method of claim 1, wherein the aqueous adhesive dispersion composition comprises the polymeric binder and one or more additives selected from the group consisting of: Surfactants, anti-settling agents, wetting agents, thickeners, rheology modifiers, short-term adhesion promoters, fillers, defoamers, pH buffers.

9. The method of claim 1, wherein the dry active powdered electrode-forming material is selected from the group consisting of: Oxides, sulfides or hydroxides of lithium and transition metals; carbonaceous materials; and nano-titanate.

10. The method of claim 1, further comprising the step of forming an energy storage device using the electrode.

11. The method of claim 1, wherein the aqueous adhesive dispersion composition consists of the polymeric binder and one or more additives selected from the group consisting of: Surfactants, anti-settling agents, wetting agents, thickeners, rheology modifiers, short-term adhesion promoters, fillers, defoamers, pH buffers.

12. An electrode formed by the method of claim 1.

Citation Information

Patent Citations

  • Aqueous polyvinylidene fluoride composition

    US20100304270A1

  • Electrode formation by lamination of particles onto a current collector

    US20110165318A9

  • Waterborne fluoropolymer composition

    US20120015246A1

  • Vinylidene fluoride polymer-based binder solution and electrode-forming composition

    US5776637A

  • Binder solution and electrode-forming composition for non-aqueous-type battery

    US6200703B1